ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA PENDUDUK LANJUT USIA DI KABUPATEN BADUNG - Astika Putra, I Kadek Yudik; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 11 (2022): vol.11.11. NOVEMBER 2022[4011-4233], 2022)
The aims of this study were 1) to analyze simultaneously the effect of non-work income, education of the elderly and the number of dependents of the elderly on the work participation of the elderly in Badung Regency. 2) to partially analyze the effect of non-work income, elderly education and the number of elderly dependents on the work participation of the elderly in Badung Regency. 3) to determine the variable that has the most dominant effect on the work participation of the elderly population in Badung Regency. This research was conducted in Mengwi District, Badung Regency. The number of samples used in this study were 100 elderly who worked using the quota sampling technique. In this study using multiple linear regression analysis technique. Simultaneously the variables of non-work income, education of the elderly and the number of dependents of the elderly have a significant effect on the work participation of the elderly in Badung Regency. Partially the non-work income variable, elderly education has a negative and significant effect on the work participation of the elderly population in Badung Regency, the number of elderly dependents partially has a positive and significant effect on the work participation of the elderly population in Badung Regency. It is hoped that the family will pay more attention to the elderly so as not to burden the elderly too much in meeting family needs. Families should pay attention and understand because with social support from a good family, it is hoped that it can help the elderly to live a better old age.